2014
DOI: 10.1093/bja/aeu088
|View full text |Cite
|
Sign up to set email alerts
|

EuroSCORE II and N-terminal pro-B-type natriuretic peptide for risk evaluation: an observational longitudinal study in patients undergoing coronary artery bypass graft surgery

Abstract: NCT00489827.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 17 publications
7
29
1
3
Order By: Relevance
“…The mechanism involved in NT-proBNP release in ischemia is not entirely clear 120 , although Xu et al observed a relationship between NT-proBNP and CAD severity 121 . The results of our study supported previous findings that showed that, in cardiac surgery, NT-proBNP levels were associated with morbidity and mortality [122][123][124][125][126] . In contrast to other studies, we found that the ability of NT-proBNP to predict severe PHF was less convincing in the context of AS 108 .…”
Section: Nt-probnp and Phfsupporting
confidence: 92%
“…The mechanism involved in NT-proBNP release in ischemia is not entirely clear 120 , although Xu et al observed a relationship between NT-proBNP and CAD severity 121 . The results of our study supported previous findings that showed that, in cardiac surgery, NT-proBNP levels were associated with morbidity and mortality [122][123][124][125][126] . In contrast to other studies, we found that the ability of NT-proBNP to predict severe PHF was less convincing in the context of AS 108 .…”
Section: Nt-probnp and Phfsupporting
confidence: 92%
“…(13) In another observational study of 365 intermediate-risk patients undergoing CABG surgery, pre-operative NT-proBNP was associated with morbidity (including renal failure) and mortality. (16) A prospective cohort including 1,559 patients undergoing on-pump cardiac surgery reported that a post-operative (day 1 and 2) BNP value >790 ng/L was associated with an adjusted HR for mortality of 2.44 (95% CI 1.65–3.62). (17) In that study, post-operative BNP had additional predictive value for 1-year mortality when combined with the logistic EuroSCORE.…”
Section: Discussionmentioning
confidence: 99%
“…(1315) Higher perioperative NT-proBNP levels have been associated with post-operative AKI, independently of EuroSCORE. (16, 17) With the imminent move towards high-sensitivity cardiac troponin assays, the prognostic value of this biomarker needs to be clarified in patients undergoing cardiac surgery. (18) In a prospective multicenter cohort of adults undergoing cardiac surgery, we aimed to evaluate whether pre- and post- operative cardiac biomarkers, including high-sensitivity cardiac troponin T (hs-cTnT), are associated with the development of severe AKI within the hospital stay, 1-year and long-term mortality after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Parece que unas cifras de GDF-15>1,8 ng/ml mejora la predicción, mientras que la presencia de NTpro-BNP alto ( punto de corte >2.000 pg/ml) o hsTNT>14 pg/ml no parece aportar mejoras. También se ha observado que al añadir los valores de troponina de la primera hora postoperatoria se detectan de forma temprana a los pacientes de alto riesgo, pero su papel en la predicción preoperatoria es menos clara 207,208,209,210 . En esta misma línea se intentó detectar moléculas como CD11b, CD 47 y CD99 para mejorar la sensibilidad y especificidad del modelo 211 .…”
Section: Escalas De Gravedad Utilizadas En Cirugiaunclassified